(untitled) (Research, Society and Development, 2021)
The practice of sports by people with disabilities has been growing more and more, bringing with it the need for greater investments in several segments, such as, for example, scientific research. Seeking to understand the phenomena that involve the athletes in their sports universe becomes relevant due to the psychological dimensions involved, knowing that they are athletes who prepare for high performance. The present research aimed to characterize the predominant psychological profiles related to the motivation and resilience of Brazilian sportspeople at school level, in addition to verifying possible associations between the psychological profile and socio-demographic and sports training factors, as well as analyzing the correlations between the dimensions explored. It was a quantitative research of a descriptive character. 114 Paralympic athletes participated at school level, from public and private Brazilian schools, of both sexes (F = 21.9%; M = 78.1%), with an average age of 15.45 years (± 1.44), with physical and visual disabilities, from 21 Brazilian states, practicing various Paralympic modalities. Participants responded to validated instruments of motivation and resilience, in addition to an anamnesis in order to characterize them. It was possible to verify that the sample was divided into two large groups of profiles, the first with high values ​​of motivation and resilience, and the second with moderate values ​​of these same variables. When analyzing socio-demographic and sports training characteristics, it was observed that only disability and age had significant values ​​of interference in this division of the subjects.